2013
DOI: 10.1016/j.bone.2013.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Studying osteocytes within their environment

Abstract: It is widely hypothesized that osteocytes are the mechano-sensors residing in bone’s mineralized matrix which control load induced bone adaptation. Owing to their inaccessibility it has proved challenging to generate quantitative in vivo experimental data which supports this hypothesis. Recent advances in in situ imaging, both in non-living and living specimens, have provided new insights into the role of osteocytes in the skeleton. Combined with the retrieval of biochemical information from mechanically stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 76 publications
0
38
0
3
Order By: Relevance
“…Until recently, much of our cell/molecular understanding of mechanosensation in bone has largely been based upon cell culture models, but over the past decade new in vivo approaches have been developed to study the osteocyte within the bone environment (11,12) . In vitro studies have identified a number of important signaling molecules that are involved in the very rapid bone cell responses to mechanical loading such as NO (13,14) , Ca +2 (15,16) , ATP (15,17) , and PGE 2 (1719) .…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, much of our cell/molecular understanding of mechanosensation in bone has largely been based upon cell culture models, but over the past decade new in vivo approaches have been developed to study the osteocyte within the bone environment (11,12) . In vitro studies have identified a number of important signaling molecules that are involved in the very rapid bone cell responses to mechanical loading such as NO (13,14) , Ca +2 (15,16) , ATP (15,17) , and PGE 2 (1719) .…”
Section: Introductionmentioning
confidence: 99%
“…It has, therefore, been hypothesized that the cell dendrites are involved in the role of the osteocytes in tissue remodeling . However, no measurements were able to support this hypothesis so far, possibly because of the lack of adequate three‐dimensional quantitative imaging modalities at the length scales of the canaliculi …”
Section: Introductionmentioning
confidence: 99%
“…(10,12,13) However, no measurements were able to support this hypothesis so far, possibly because of the lack of adequate three-dimensional quantitative imaging modalities at the length scales of the canaliculi. (14) In the past, 3D imaging of the lacuno-canalicular network (LCN) has mainly been carried out using confocal microscopy, (15,16) which has two disadvantages: a limited resolution of about 300 nm and a penetration depth of approximately 60 mm. (17) Ptychographic X-ray CT and mCT have been demonstrated as feasible to resolve the 3D LCN with submicron resolution.…”
Section: Introductionmentioning
confidence: 99%
“…From when they become enclosed within this mineralised tissue they are labelled as osteocytes, contained within interconnected voids called osteocyte lacunae. As such, lacunae provide a hard-tissue record of the osteocyte morphology (Franz-Odendaal et al, 2006;Bonewald, 2011;Webster et al, 2013), which varies according to that of the extracellular collagen matrix deposited during bone growth and remodelling (Amprino, 1947;Marotti, 1979;de Ricqlès et al, 1991;Kerschnitzki et al, 2011;van Oers et al, 2015). Therefore, the morphology of osteocyte lacunae has relevance to the study of bone development and osteocyte function among other topics.…”
Section: Introductionmentioning
confidence: 99%